Optimizing Individual Resilience Through The Tazkiyatun Nafs Method: Implications For Islamic Education At The Al-Mu’min Rehabilitation Foundation In Malang - Hadiyatullah, Zainur Rofiq (LP2M IAIN kUDUS, 2025)
This study examines the implementation of Tazkiyatun Nafs in improving individual resilience at Al-Mu'min Rehabilitation Foundation Malang through a religious education approach. Using qualitative methods through observation, interviews, and documentation, this study found that the approach of purifying the soul through Takhalli (cleansing bad traits) and tahalli (filling noble morals) contributes to building individual psychological resilience. Spiritual interventions, such as zikr, congregational prayers, and therapist guidance, are proven to help clients overcome drug addiction and mental disorders by increasing equanimity, perseverance, and religious awareness. The results showed that the Tazkiyatun Nafs method has several implications in improving individual resilience, namely: (1) Negative Emotion Management, where individuals learn to control stress and anxiety through consistent worship practices; (2) Mental and Spiritual Resilience, which is obtained through increased faith and piety; (3) Increased Religious Values, which have an impact on spiritual transformation and individual morality; and (4) Formation of Harmonious Social Relationships, with social support that helps individuals build healthier and more positive relationships. These findings are in line with the Wagnild-Young resilience model and the Snyder-Lopez variable-focused model, which emphasize the importance of internal-external factor interactions in building resilience. Thus, Tazkiyatun Nafs-based religious education at Al-Mu'min Foundation not only functions as a therapeutic method, but also as a means of Islamic character building that strengthens individual resilience in facing life's challenges.